(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Foreign body ingestion is common in children; however, ingestion of sharp objects such as hijab pins poses a significant risk of gastrointestinal complications. We report a case of a 7- year-old female who presented with delayed referral after ingestion of a hijab pin. Serial radiographs demonstrated persistent localization of the foreign body, ultimately requiring surgical intervention. The foreign body was found impacted in the second part of the duodenum and was successfully removed by enterotomy. This case highlights the importance of early referral and timely intervention in sharp foreign body ingestion. Journal of Paediatric Surgeons of Bangladesh (2024) Vol. 15 (1 & 2): 44-45